(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the key aspect in organizing cultural events – the requirements for scriptwriting – and explores, within the pedagogical context, the factors of professional competence in scriptwriting identified through the process of developing students’ skills in this field.